Acylated ghrelin limits fat accumulation and improves redox state and inflammation markers in the liver of high‐fat‐fed rats. (13th June 2013) - Barazzoni, Rocco; Semolic, Annamaria; Cattin, Maria Rosa; Zanetti, Michela; Guarnieri, Gianfranco
<x xml:space="preserve">Abstract</x> Objective Obesity commonly causes hepatic lipid accumulation that may favor oxidative stress and inflammation with negative clinical impact. Acylated ghrelin (A‐Ghr) modulates body lipid distribution and metabolism, and it may exert antioxidant effects in vitro as well as systemic anti‐inflammatory effects in vivo. The impact of A‐Ghr on liver triglyceride content, redox state and inflammation markers in diet‐induced obesity was investigated. Design and Methods A‐Ghr (200‐μg/injection: HFG) or saline (HF) were administered subcutaneously twice‐daily for 4 days to 12‐week‐old male rats fed a high‐fat diet for 1 month (n = 8–10/group). Results Compared to lean animals, liver triglyceride accumulation occurred in HF despite enhanced phosphorylation of the lipid oxidation regulator AMPK and preserved mitochondrial enzyme activities. High triglycerides were accompanied by pro‐oxidant changes in redox state and proinflammatory changes in NF‐kB and TNF‐alpha. A‐Ghr limited liver triglyceride excess (P < 0.05 HF > HFG > Control) with concomitant activation of glutathione peroxidase and normalized redox state and cytokines. A‐Ghr‐induced liver changes were associated with higher plasma adiponectin and lower circulating fatty acids (P < 0.05 HFG vs. HF). Conclusions A‐Ghr limits liver triglyceride accumulation and normalizes tissue redox state and inflammation markers in diet‐induced obese rats. These results suggest a favorable impact of A‐Ghr on hepatic complications of diet‐induced obesity.